Eksplorasi Kecepatan Perhitungan Aplikasi Matematika pada Windows (98, Me, Xp, 7, 8) - Felix Adrianto; Inez Gavrila Wahyudi; Jovis Tanner (ULTIMA InfoSys, 2013)
This research aims to give information regarding the speed of mathematical calculation on windows so that people can choose an operating system which suits them without wasting their time. In this research, we need a laptop and some operating systems (windows) so that we can compare one with the other accurately. The result of this research will be noted and analysed qualitatively, quantitatively, and descriptively. It shows that running the same mathematical calculation program on different operating systems will produce a same result but different time. Index Terms - calculate the speed, operating system